Contributions to knowledge of Arthrobrachus Solier,1849 (Coleoptera: Melyridae). A redescription of Arthrobrachus forsteri Wittmer, 1958 and A. longipilis Pic, 1919 - Estrada M., Patricia (Zootaxa, 2020)
The study of the types of Arthrobrachus forsteri and A. longipilis, the last two pending revision until now, allows to recognize them as valid species of the genus Arthrobrachus. With this the number of valid species of the genus is 20. In this paper, both taxa are redescribed alongside their distribution data.